Grenzen und Reichweiten Nationaler Innovationssysteme und forschungspolitische Implikationen - Alfred Spielkamp (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1997)
Die vorliegenden Überlegungen sind darauf gerichtet, die Ideen und wesentlichen Gedanken Nationaler Innovationssysteme aufzugreifen und in den Kontext einer wissensbasierten Ökonomie zu stellen. Neben den Akteuren oder Spielern geht es um die Regeln und Funktionsmechanismen und schließlich die Rolle politischer Instanzen im Innovationsnetzwerk; die Rolle(n), die sie sich selbst zuweisen, und die Rolle(n), die sie aufgrund des Verhaltens der Akteure ausfüllen sollten. Die theoretischen Überlegungen werden dabei auf empirische Ergebnisse gestützt, die insbesondere die Grenzen und Reichweiten derartiger Systeme sichtbar machen und damit die politischen Zuständigkeiten. Den Abschluß finden die Ausführungen in dem Versuch anzudeuten, wie eine Anpassung und Neugestaltung der Politikfelder oder Kompetenzbereiche an die Bedürfnisse der Unternehmen im nationalen Innovationsnetz aussehen könnte. – – This paper deals with flows of technology and information among people and institutions and the role of public support given by different sponsors (the federal government, the Länder and the European Union). Recent theory stresses the importance of the interactions and linkages among acteurs and institutions involved in innovation and technology development of a country and calls such a web of interaction a national innovation system. The theoretical and empirical analyses on national systems of innovation lead to the conclusion that countries differ in the way in which knowledge flows and that innovation takes place in a specific national context. Therefore, for policy makers an understanding of the system is seen as a key to improve the technology performance. That means that a detailed picture of what is happening inside the economy and what is relevant to the different needs and wants of enterprises is the basis for promotion programmes and policy actions. On the basis of some theoretical comments and empirical findings we will discuss how a national innovation system works, how firms use the system as well as promotion programmes given by different sponsors, and how a matching of the public 2 2 support and a focusing of firms specific demand could contribute to a more efficient R&D policy.
Keywords: 330; Innovation; Forschung; Netzwerk; Staatliche Einflussnahme; Forschungs- und Technologiepolitik; Deutschland; Theorie; EU-Staaten